88.5k views
3 votes
Let f(x)=2/x-3. Find f^-1(x)

1 Answer

5 votes

Answer:

Two questions:

Question 1:
f^(-1)(x)=? given
f(x)=(2)/(x)-3.

Answer 1:
f^(-1)(x)=(2)/(x+3)

Question 2:
f^(-1)(x)=? given
f(x)=(2)/(x-3).

Answer 2:
f^(-1)(x)=(2)/(x)+3

Explanation:

So
f^(-1) is used in most classes to represent the inverse function of
f.

The inverse when graphed is a reflection through the y=x line. The ordered pairs
(a,b) on
f implies
(b,a) are on
f^(-1).

This means we really just need to swap x and y.

Since we want to write as a function of x we will need to solve for y again.

Question 1:


y=(2)/(x)-3

Swap x and y:


x=(2)/(y)-3

We want to solve for y.

Add 3 on both sides:


x+3=(2)/(y)

Make the left hand side a fraction so we can cross-multiply:


(x+3)/(1)=(2)/(y)

Cross multiply:


y(x+3)=1(2)

Simplify right hand side:


y(x+3)=2

Divide both sides by (x+3):


y=(2)/(x+3)

So
f^(-1)(x)=(2)/(x+3).

Question 2:


y=(2)/(x-3)

Swap x and y:


x=(2)/(y-3)

Make left hand side a fraction so we can cross multiply:


(x)/(1)=(2)/(y-3)

Cross multiply:


(y-3)x=1(2)

We have to distribute here:


yx-3x=2

Add 3x on both sides:


yx=2+3x

Divide boht sides by x:


y=(2+3x)/(x)

You could probably stop here but you could also simplify a little.

Separate the fraction into two terms since you have 2 terms on top bottom being dividing by x:


y=(2)/(x)+(3x)/(x)

Simplify second fraction x/x=1:


y=(2)/(x)+3

So
f^(-1)(x)=(2)/(x)+3.